SOSIALISASI EDUKASI KEGIATAN YANG MEMBAHAYAKAN PESAWAT DI KAWASAN KESELAMATAN OPERASI PENERBANGAN BANDARA SMB II PALEMBANG - Herlina Febiyanti; Dwi Candra Yuniar; Bambang Wijaya Putra; I Gusti Agung Ayu Mas Oka; Muhammad Syahrul Munir; Muhammad Erawan Destyana; Muhammad Al Hafied; Vania Nadhifa Azzahra; Nabila Azzahra (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
The purpose of this socialization was to provide education to the people around Sultan Mahmud Badaruddin (SMB) II Palembang Airport about activities that can endanger flights, so that things that endanger flights caused by community activities can be avoided. The socialization method used was exposure by experts and discussions with people living near SMB II Palembang Airport. The results obtained from this socialization are that the participants (community) understand what activities endanger aircraft, especially in the flight operation safety area of SMB II Palembang Airport. The results of the socialization have been published on the Palembang Aviation Polytechnic social media.